The method of capsuloplasty in elimination of persistent extension contractures of the knee joint - Barkov, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
Treatment of persistent extension contractures of the knee joints is a rather difficult challenge. It is possible to eliminate a persistent contracture only with help of surgery and subsequent conservative treatment. It is effective to replace a defect in the knee joint capsule with a flap of one’s own femoral fascia in compliance with the technique suggested.